Approaches to contemporary Central American theater - Corrales Arias, Adriano (2021)
What follows is an interpretive essay on the actuality of theater activity in Central America. It is proposed as an input or approach for a debate, which should lead to certain levels of dialogue and possible more or less practical approaches to the problem raised, as well as the possibility of mapping and “reconstructing” what happens in the irregular scene of the region.